2006
DOI: 10.1155/mpe/2006/98171
|View full text |Cite
|
Sign up to set email alerts
|

The SM/M/N queueing system with broadcasting service

Abstract: We consider a multiserver queueing model with the semi-Markovian arrival process and exponential service time distribution. Novel customers admission discipline is under study. The customer, which sees several free servers upon arrival, is served simultaneously by all these servers. Such situation occurs, for example, in modeling wireless communication network with broadcasting. Systems with infinite buffer and with losses are investigated. Stationary distributions of a queue, waiting and sojourn times, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
3
0
4
Order By: Relevance
“…Besides this reliability aspect, parallel handling of query by several agents can decrease response time because the response time in this case is the minimum of durations of handling the query by all involved agents. The results from the field of Queueing Systems [7] have shown that this kind of assumptions is reasonable and allows for achieving a higher performance (comparing with standard one query-one agent systems) in case the arrival rate of the queries is not very high.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Besides this reliability aspect, parallel handling of query by several agents can decrease response time because the response time in this case is the minimum of durations of handling the query by all involved agents. The results from the field of Queueing Systems [7] have shown that this kind of assumptions is reasonable and allows for achieving a higher performance (comparing with standard one query-one agent systems) in case the arrival rate of the queries is not very high.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Erlang in the beginning of the 20th century. The BC discipline was investigated recently in the framework of the more general SM/PH/N queueing model in the paper (Lee et al 2006). The following assertion stems from (Lee et al 2006).…”
Section: Lemmamentioning
confidence: 99%
“…Системотехническое проектирование сис-тем обработки данных базируется на использовании математического аппарата теории массового обслу-живания, теории надежности [6,[18][19][20][21][22][23][24].…”
Section: Introductionunclassified
“…Модели систем с резервированным обслуживанием запросов для многоканальной системы с общей очередью предложены в работах [18,19]. В моделях [18,19], если чис-ло занятых приборов в момент поступления запроса меньше некоторого порогового значения, то запрос копируется, а его копии обслуживаются всеми свободными приборами. Если число занятых приборов в момент поступления запроса не меньше этого порогового значения, то запрос обслуживается одним при-бором.…”
Section: Introductionunclassified
See 1 more Smart Citation